A truncated form of rod photoreceptor PDE6 β-subunit causes autosomal dominant congenital stationary night blindness by interfering with the inhibitory activity of the γ-subunit. - Gaël Manes; Pallavi Cheguru; Anurima Majumder; Béatrice Bocquet; Audrey Sénéchal; Nikolai O Artemyev; Christian P Hamel; Philippe Brabet (PLoS ONE)
Autosomal dominant congenital stationary night blindness (adCSNB) is caused by mutations in three genes of the rod phototransduction cascade, rhodopsin (RHO), transducin α-subunit (GNAT1), and cGMP phosphodiesterase type 6 β-subunit (PDE6B). In most cases, the constitutive activation of the phototransduction cascade is a prerequisite to cause adCSNB. The unique adCSNB-associated PDE6B mutation found in the Rambusch pedigree, the substitution p.His258Asn, leads to rod photoreceptors desensitization. Here, we report a three-generation French family with adCSNB harboring a novel PDE6B mutation, the duplication, c.928-9_940dup resulting in a tyrosine to cysteine substitution at codon 314, a frameshift, and a premature termination (p.Tyr314Cysfs*50). To understand the mechanism of the PDE6β1-314fs*50 mutant, we examined the properties of its PDE6-specific portion, PDE6β1-313. We found that PDE6β1-313 maintains the ability to bind noncatalytic cGMP and the inhibitory γ-subunit (Pγ), and interferes with the inhibition of normal PDE6αβ catalytic subunits by Pγ. Moreover, both truncated forms of the PDE6β protein, PDE6β1-313 and PDE6β1-314fs*50 expressed in rods of transgenic X. laevis are targeted to the phototransduction compartment. We hypothesize that in affected family members the p.Tyr314Cysfs*50 change results in the production of the truncated protein, which binds Pγ and causes constitutive activation of the phototransduction thus leading to the absence of rod adaptation.